Low Back Pain E/C Musculoskeletal Disorder (Msds) In Workers With Sitting Body Positions - Martha, Anastasia Putu; Djoar, Raditya Kurniawan; Gerhanawati, Ifa; Swandari, Atik (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2023)
The muscles that are often disturbed are the muscles of the neck, arms, hands, fingers, back, waist and lower muscles. Working for a long time in a fixed position, especially sitting, will cause discomfort. This working attitude creates a static workload on the lower back muscles and causes lower back pain in workers. Respondents involved in this study amounted to 49 respondents. All respondents have the dominant activity at work, namely sitting. When viewed from the character of the respondents, as much as 77.55% of respondents had experienced muscle complaints. The most frequent muscle complaints were in the area of ??the waist (53.06%), buttocks (44.90%) and neck and shoulders (42.86%). The longer a person sits there will be stretching of the back muscles and the posterior longitudinal ligament which have the thinnest properties so that this prone area is disturbed causing pain. Suggestions for employees who sit for a long time, namely doing short sports on the sidelines of work and modifying the work environment so that the sitting position becomes ergonomic